¿Sabemos lo que estamos conservando? Peces del Parque Nacional Aconquija, Tucumán, Noroeste de Argentina - Saravia, Alejandro Nicolas (2023)
Aconquija is the only National Park (NP) in the province of Tucumán and one of the most important in northwestern Argentina. It is the NP with wider altitudinal gradient in the country (Administración de Parques Nacionales, 2023), ranging from 511 to 5450 m.a.s.l. Given that this NP was recently created, most of its territory has yet to be investigated regarding its diversity of species. Water bodies in this area are represented by mountain rivers and streams draining to the Salí-Dulce River basin. The current study provides a species list of freshwater fishes inhabiting the Aconquija National Park. We examined 427 specimens, distributed in five orders, ten families and 20 species.